President and leader: Charles de Gaulle and French independence - Kebadze, Madona (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2026)
Charles de Gaulle stands as one of the most influential political leaders of the twentieth century, whose vision and leadership profoundly reshaped France’s political institutions, foreign policy orientation, and national identity. This article critically examines de Gaulle’s pursuit of French sovereignty and strategic autonomy within the broader theoretical frameworks of nationalism, state sovereignty, and political leadership. By employing qualitative historical analysis and interpretive political methodology, the study explores how de Gaulle transformed France’s domestic governance through the establishment of the Fifth Republic and redefined its international role by pursuing an independent foreign and defense policy during the Cold War. Particular attention is paid to France’s withdrawal from NATO’s integrated military command, the development of an autonomous nuclear deterrent, and de Gaulle’s pragmatic approach to decolonization, especially in Algeria. The research builds on previous analyses by integrating detailed case studies of French institutional reforms, diplomatic correspondence, and domestic political debates, thereby providing a more nuanced understanding of Gaullism as a framework for political sovereignty and the reconstruction of national identity. The findings suggest that de Gaulle’s policies not only restored France’s global status but also created a lasting model of strategic autonomy that continues to shape French political identity. This study adds to current debates on leadership, sovereignty, and post-imperial state change by providing a comprehensive view of Gaullism as both a political doctrine and a durable framework for national independence.